History of Mathematics and History of Science: Some remarks concerning contextual framework - SAITO, FUMIKAZU (Educação Matemática Pesquisa Revista do Programa de Estudos Pós-Graduados em Educação Matemática, 2012)
Abstract This essay is devoted to the contextual methodology in History of Mathematics. The author discusses the contextual approach given by new trends in historiography in history of science and suggests that this could help to renew the contextual framework in history of mathematics. Here we base our study on primary-sources research and survey. Special attention is given to a set of documents concerning mathematical instruments which could convey a new appreciation of mathematical practices in the sixteenth and seventeenth centuries. Resumo Este ensaio é dedicado à metodologia contextual em História da Matemática. O autor discorre sobre a abordagem contextual das novas tendências historiográficas em História da Ciência, sugerindo que tal abordagem poderia auxiliar na renovação do quadro contextual em história da matemática. Este ensaio tem por base pesquisas e levantamento pautados em fontes primárias. Especial atenção é dada a um conjunto de documentos relativos a instrumentos matemáticos que oferecem uma nova visão das práticas matemáticas nos séculos XVI e XVII.